Efficient antisense inhibition reveals microRNA-155 to restrain a late-myeloid inflammatory programme in primary human phagocytes. Issue 5 (4th May 2021) - Linden, Greta; Janga, Harshavardhan; Franz, Matthias; Nist, Andrea; Stiewe, Thorsten; Schmeck, Bernd; Vázquez, Olalla; Schulte, Leon N
ABSTRACT: A persisting obstacle in human immunology is that blood-derived leukocytes are notoriously difficult to manipulate at the RNA level. Therefore, our knowledge about immune-regulatory RNA-networks is largely based on tumour cell-line and rodent knockout models, which do not fully mimic human leukocyte biology. Here, we exploit straightforward cell penetrating peptide (CPP) chemistry to enable efficient loss-of-function phenotyping of regulatory RNAs in primary human blood-derived cells. The classical CPP octaarginine (R8) enabled antisense peptide-nucleic-acid (PNA) oligomer delivery into nearly 100% of human blood-derived macrophages without apparent cytotoxicity even up to micromolar concentrations. In a proof-of-principle experiment, we successfully de-repressed the global microRNA-155 regulome in primary human macrophages using a PNA-R8 oligomer, which phenocopies a CRISPR-Cas9 induced gene knockout. Interestingly, although it is often believed that fairly high concentrations (μM) are needed to achieve antisense activity, our PNA-R8 was effective at 200 nM. RNA-seq characterized microRNA-155 as a broad-acting riboregulator, feedback restraining a late myeloid differentiation-induced pro-inflammatory network, comprising MyD88-signalling and ubiquitin-proteasome components. Our results highlight the important role of the microRNA machinery in fine-control of blood-derived human phagocyte immunity and open the door for further studies on regulatory RNAs in difficult-to-transfect primary human immune cells.